Organizational culture study as the system element of internal business communication - Liudmyla Kompaniiets (Cхід)
The issue is devoted to the study of modern processes in the sphere of decision-making and organizational communicational systems building. The complex analysis of organizational culture as a component of social culture, system of values and beliefs, which determined personnel’s behavior model and conditioned the general character of organization existence is performed. In particular, applying to comparative and critical analysis of various concept definitions of “organizational culture” and revealing the advantages of social and cultural approach as a platform for social structures analysis which formed value background for managerial decisions, the author considers organizational culture as a base for effective managerial decisions-making; defines the main classification principles of organizational culture; determines the structure on the ground of three-level conception: “surfaced”, “beneath surface” and “deep” levels, which form “cultural paradigm” of an organization and coherent image. Furthermore, the typical internal components of organizational culture are highlighted and analyzed. Addressing the following objectives provides an opportunity, firstly, to organize social and philosophical concepts’ analysis of organizational culture on global and local levels, whereas each relates to a special tool standard used within social and communication analysis; secondly, to define specific features’ selection of organizational culture’s influential factors on managerial decisions creation and their mechanisms of implementation. The crucial conclusions are: mutual connection determination between 1) the types of social structure and the peculiarities of organizational activity; 2) the classification features of organizational culture and intentions of managerial decisions; 3) levels of organizational culture and organizational values positioning; 4) a personal type and his ability to accept and transmit the fundamental achievements of organizational culture.